Accounting for Employee Stock Options - Guay, Wayne; Kothari, S. P; Sloan, Richard (American Economic Review, 2003)
Employee stock options (ESO’s) are a ubiquitous form of compensation in corporate America. By the late 1990’s, ESO’s outstanding at large corporations averaged 7 percent of total outstanding shares, with top executives holding approximately one-third of total ESO’s (John Core and Guay, 2001). Empirical evidence suggests that firms use ESO’s to align employees’ and shareholders’ interests, attract and retain employees, and compensate employees for their labor while simultaneously raising capital from employees (Core and Guay, 1999, 2001; Kevin J. Murphy, 1999). There is currently an intense debate nationally and internationally among standard-setters, politicians, investors, corporate executives, and academics about whether to require corporations to deduct the estimated value of ESO grants as a business expense in reported income. Existing accounting standards require firms to expense most forms of pay, such as salaries, cash bonuses, and the value of stock grants, but allow firms to choose whether to expense the value of ESO grants. Until very recently, nearly all firms chose not to expense ESO’s. However, firms that do not expense ESO’s must publicly disclose in the financial statement footnotes what reported income would have been if the ESO’s were expensed. In a recent sample of large growth firms, Christine Botosan and Marlene Plumlee (2001) find that mandatory expensing of ESO’s would have resulted in a 14-percent median reduction in firms’ earnings per share. Firms are also required to disclose details of top-executive ESO compensation in the annual proxy statement. Underlying the ESO debate is the concern that the choice among alternative financialaccounting treatments have real economic consequences. A large literature beginning with Ross Watts and Jerold Zimmerman (1978) provides evidence that accounting choice can impose economic costs on firms when contracts (e.g., debt and executive compensation contracts) or influential external parties (e.g., tax authorities) rely on reported accounting numbers (see Thomas Fields et al. [2001] for a survey of this literature). Accounting choice can also have economic consequences if investors fixate on particular numbers, such as reported earnings, resulting in security mispricing and misallocation of capital. Proponents of mandatory expensing argue that ESO’s reflect a cost of acquiring employee labor, and that expensing ESO’s conveys this information to outsiders consistently with other labor costs. Some argue that the absence of ESO expense results in stock mispricings, because investors fixate on reported earnings and fail to understand or utilize supplemental footnote disclosures about the true economic cost of ESO grants. Others argue that, when investors and boards of directors fixate on accounting earnings, the absence of ESO expense exacerbates ineffective corporate governance and allows management to use ESO’s to extract excessive compensation. Proponents of this view argue that expensing ESO’s will reign in management compensation by putting it under a brighter light. Opponents of expensing ESO’s argue that deducting the cost of ESO’s from earnings conveys an impression of weaker financial results to investors and, under the assumption that investors fixate on reported earnings, could raise the firms’ cost of financing and stifle corporate investment and innovation. There is also a concern that external parties, such as taxing authorities, might use changes in financial-accounting treatment as a cue to alter regulatory and tax policy.